Studi Literature Model Problem Based Learning - Dinelti Fitria; Lufri; Ali Imran; Yuni Ahda (CV. AFDIFAL MAJU BERKAH, 2022)
One method that can help students in the learning process is problem based learning. Problem based learning is one of the constructivist learning flow models that requires students to observe the reality contained in everyday life. The purpose of writing this paper is to dig deeper based on a literature study on the definition of problem based learning, characteristics of problem based learning, theoretical basis of problem based learning, steps of problem based learning, evaluation of problem based learning, advantages and disadvantages of problem based learning. From various written sources, it can be concluded that learning Problem Based Learning is obtained some basic values ​​that must be developed by the teacher in enlivening the learning atmosphere, here the teacher does not only act as the main subject in learning but on the other hand the teacher must involve students so that students' critical thinking skills can develop.